Review of the electronic book “Global Optimization with Maple” by János D. Pintér - Forst, Wilhelm (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2007)
We review the recent e-book authored by János D. Pintér, Global Optimization with Maple, Maplesoft and Pintér